SURVEY REPORT ON NEW INFORMATION INTEGRATION - I Wayan Simri Wicaksana (Jurnal Sistem Informasi, 2005)
Information integration has been developping for fullfill some needs at many areas. Currently, there are still many challenging in information integration issues. One of the main trigger in information integration is internet, web, ‘easier’ to develop electronic data and distributed computing infrastructure. There are many questions arise in information integration. What are the requirements changed over time? What key progress has been made? How in the future?. The meaning of information integration are involve information interoperability, information sharing. Information and data definition in this paper is described as data is a source of information. Therefore, sometime, using of terminology data and information is changeable. Refer to current condition, to decide it is data or information depends on point of view user. Many afford in research and industrial practices have been introduced since two decades. From effort in transfer file, federate, until semantic mediation, and information broker have been done and still continue until today. The challenges for today information integration are well understood. Information integration purpose is in order to manage and use information effectively. Find new approach to overcome previous problem will be still continues. This report contains a survey on some approach of information integration. The paper will be divided in four sections. First section writes about introduction and generation of information integration as a background theory talk in section two. Section four points out some ‘new’ information integration approach. And the last section gives summary of the paper.Keywords : survey, information integration